2015
DOI: 10.1164/rccm.201411-1990oc
|View full text |Cite
|
Sign up to set email alerts
|

Serum Apolipoprotein A-I and Large High-Density Lipoprotein Particles Are Positively Correlated with FEV1 in Atopic Asthma

Abstract: Rationale: Although lipids, apolipoproteins, and lipoprotein particles are important modulators of inflammation, varying relationships exist between these parameters and asthma.Objectives: To determine whether serum lipids and apolipoproteins correlate with the severity of airflow obstruction in subjects with atopy and asthma.Methods: Serum samples were obtained from 154 atopic and nonatopic subjects without asthma, and 159 subjects with atopy and asthma. Serum lipid and lipoprotein levels were quantified usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
56
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 49 publications
(58 reference statements)
11
56
2
Order By: Relevance
“…For example, a positive correlation was found between serum apoA-I levels, as well as HDL, and higher FEV 1 in a cohort of 159 subjects with atopic asthma, whereas a similar positive correlation was found in an analysis of the 14,135 subjects without respiratory disease who participated in the Third National Health and Nutrition Examination Survey (73,74). These studies suggest that circulating levels of apoA-I may have a protective effect on airflow obstruction in asthma.…”
Section: Apoa-i and Asthmamentioning
confidence: 69%
“…For example, a positive correlation was found between serum apoA-I levels, as well as HDL, and higher FEV 1 in a cohort of 159 subjects with atopic asthma, whereas a similar positive correlation was found in an analysis of the 14,135 subjects without respiratory disease who participated in the Third National Health and Nutrition Examination Survey (73,74). These studies suggest that circulating levels of apoA-I may have a protective effect on airflow obstruction in asthma.…”
Section: Apoa-i and Asthmamentioning
confidence: 69%
“…40 Furthermore, serum samples were analyzed by using nuclear magnetic resonance spectroscopy to identify the subset of HDL particles that mediated the association with FEV 1 . This technique measures the nuclear magnetic resonance proton signal from the terminal methyl group on lipids to determine the amount of each type of lipoprotein particle and also categorizes lipoprotein particles based on size.…”
mentioning
confidence: 99%
“…Using multivariate logistic regression models, they reported that while plasma ApoB concentrations were not associated with symptoms of either asthma or allergy, serum ApoA1 levels significantly correlated with a high prevalence of atopic or nonatopic wheeze and asthma. In a recent but smaller study, Barochia et al [38 ]assessed the abovementioned findings. They enrolled 154 atopic and not atopic adult subjects without asthma, and 159 subjects with atopy and asthma.…”
Section: Resultsmentioning
confidence: 99%
“…Serum lipoprotein levels and airflow obstruction were assessed using standard diagnostic assays, and nuclear magnetic resonance and spirometry, respectively. They reported that HDL cholesterol (HDL-C) and ApoA1 were positively correlated with forced expiratory volume in the 1st second (FEV 1 %) in subjects with atopy and asthma, but there was a negative correlation between FEV 1 % and serum levels of TG, LDL-C, ApoB, and the ApoB/ApoA1 ratio [38]. Previously, in 24 asthmatic patients, Scichilone et al [39 ]detected serum LDL subclass levels and a severe degree of airflow obstruction (FEV 1 %) and vital capacity (VC%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation